THE EFFECT OF THE PROJECT-BASED LEARNING MODEL ON STUDENTS' SCIENCE LITERACY SKILLS AND SELF-EFFICACY - Dwi Anjli; Muliani Muliani; widya widya; syarifah rita zahara; riza andriani; nanda novita; syafrizal idris (JURNAL EDUSCIENCE, 2023)
This research aims to investigate the influence of the project-based learning instructional model on students' science literacy skills and self-efficacy in rectilinear motion kinematics at SMA Negeri 1 Lhokseumawe. The research design employed is a quasi-experiment in the form of a Nonequivalent (Pretest And Posttest) Control Group Design. The study population consists of ten classes of eleventh-grade IPAS students at SMA Negeri 1 Lhokseumawe. The sampling technique used is purposive sampling, with XI IPAS 1 (36 students) selected as the experimental class using the PjBL learning model and XI IPAS 4 (36 students) as the control class using the direct instruction learning model. Data collection is conducted through a 10-item essay test and a non-test questionnaire on student self-efficacy comprising 20 statements. Data analysis utilizes the Manova test. This research indicates that the PjBL learning model impacts science literacy skills based on the Manova test results, which show 0.000 < 0.05, signifying a significant influence on the average science literacy skills. The PjBL learning model also influences self-efficacy according to the Manova test results, which demonstrate 0.004 < 0.05, indicating a significant impact on the average self-efficacy. Furthermore, the PjBL learning model affects science literacy skills and self-efficacy, as evidenced by the important results of the Manova test, 0.000 < 0.05. Therefore, it can be concluded that the null hypothesis  is rejected, and the alternative hypothesis is accepted. Based on this, it can be inferred that the PjBL learning model influences the science literacy skills and self-efficacy of grade XI students at SMA Negeri 1 Lhokseumawe.Keywords: Project-Based Learning Model, Science Literacy Skills, Self-Efficacy